PREVENTION EFFORT OF SEXUAL VIOLENCE FROM POWER INEQUALITY RELATIONS IN ISLAMIC BOARDING SCHOOLS IN INDONESIA - Moh Ashif Fuadi; Rosyadi, Muhammad Husna; Mega Alif Marintan; Qisthi Faradina Ilma Mahanani; Muhammad Aslambik (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
Abstract This study investigates the prevention efforts against sexual violence in Islamic boarding schools (pesantren) in Indonesia, focusing on implemented strategies. Conducted using a quantitative survey with a descriptive design, data were gathered via questionnaires distributed across various pesantren. Results reveal that prevention is facilitated by studying specific texts on sex education like 'Uq┼½du al-Lujain, Qurratul' Uy┼½n, and Fathul Iz─ür. Additional measures include monitoring student communications via mobile phones, imparting advice (mau'idzoh) from religious teachers (Kiai), and enforcing strict rules on interactions between genders. The study identifies power imbalances as contributing factors, where higher-ranking individuals exploit authority to exert control. Implications suggest that sexual violence erodes public trust, necessitating collaborative preventive actions involving pesantren, communities, and government. Furthermore, stringent legal measures against perpetrators are crucial. This research significantly contributes to the literature on sexual violence prevention in religious educational settings, advocating a comprehensive approach encompassing education, supervision, and robust law enforcement to combat this issue effectively. Abstrak Studi ini menyelidiki upaya pencegahan terhadap kekerasan seksual di pesantren-pesantren di Indonesia, dengan fokus pada strategi yang diterapkan. Dilakukan menggunakan survei kuantitatif dengan desain penelitian deskriptif, data dikumpulkan melalui kuesioner yang disebar di berbagai pesantren. Hasil penelitian menunjukkan bahwa pencegahan difasilitasi melalui studi teks-teks khusus tentang pendidikan seks seperti 'Uq┼½du al-Lujain, Qurratul' Uy┼½n, dan Fathul Iz─ür. Langkah-langkah tambahan meliputi pemantauan komunikasi siswa melalui telepon genggam, pemberian nasihat (mau'idzoh) dari guru agama (Kiai), dan penegakan aturan ketat mengenai interaksi antara gender. Studi ini mengidentifikasi ketidakseimbangan kekuasaan sebagai faktor penyumbang, di mana individu dengan posisi lebih tinggi mengeksploitasi otoritas untuk mengendalikan orang lain. Implikasi dari temuan ini menyarankan bahwa kekerasan seksual merusak kepercayaan publik, memerlukan tindakan preventif kolaboratif yang melibatkan pesantren, masyarakat, dan pemerintah. Selain itu, tindakan hukum yang ketat terhadap pelaku sangat penting. Penelitian ini memberikan kontribusi signifikan terhadap literatur tentang pencegahan kekerasan seksual di lembaga pendidikan agama, mendorong pendekatan komprehensif yang mencakup pendidikan, pengawasan, dan penegakan hukum yang kuat untuk mengatasi masalah ini secara efektif.